Strangulated internal hernia following severe ovarian hyperstimulation syndrome: a case report. (2nd January 2021) - Wei, Likun; Zhang, Yanfang; Song, Xueru
Abstract: Ovarian hyperstimulation syndrome (OHSS) is a serious complication of ovarian stimulation. Herein, we report a rare case of strangulated internal hernia in a woman with severe OHSS following ovulation induction. A delay in the diagnosis and management of acute abdominal pain can lead to serious problems. The aim of this case report was to highlight the diagnostic difficulties of abdominal pain in women with OHSS, and emphasize the positive effects of imaging and a timely differential diagnosis in clinical practice.